Study of Activated Carbon Supported Nickel Catalyst for Adsorption of Phenolic Wastewater - Li, Hao; Li, Xinyao; Hou, Yanmin; Zhao, Xiaojun (Asian Journal of Chemistry, 2017)
Phenolic wastewater containing p-chlorophenol and o-chlorophenol can be adsorbed by activated carbon. This procedure reduces the COD value. In order to raise the adsorptivity of activated carbon for organic pollutants in phenolic effluent, the synthesis of activated carbon supported nickel catalyst was prepared and used in the treatment of phenolic wastewater, the affect factor and mechanism were investigated. The results showed that the adsorption capacity improved significantly because of the coordination between nickel and hydroxyl functional groups existed in the phenolic. Maintaining temperature at 25 °C, pH at 6, 2 h of reaction time and 40 mg/L of H2O2, the degradation rate of chlorophenol exceeded 80 %. This method incorporated adsorption and catalytic oxidation. It has important action for the practice and extension of catalytic wet oxidation.